Amphetamine sensitisation and memory in healthy human volunteers: A functional magnetic resonance imaging study. (September 2014) - O'Daly, Owen G; Joyce, Daniel; Tracy, Derek K; Stephan, Klaas E; Murray, Robin M; Shergill, Sukhwinder
Amphetamine sensitisation (AS) is an established animal model of the hypersensitivity to psychostimulants seen in patients with schizophrenia. AS also models the dysregulation of mesolimbic dopamine signalling which has been implicated in the development of psychotic symptoms. Recent data suggest that the enhanced excitability of mesolimbic dopamine neurons in AS is driven by a hyperactivity of hippocampal (subiculum) neurons, consistent with a strong association between hippocampal dysfunction and schizophrenia. While AS can be modelled in human volunteers, its functional consequences on dopaminoceptive brain regions (i.e. striatum and hippocampus) remains unclear. Here we describe the effects of a sensitising dosage pattern of dextroamphetamine on the neural correlates of motor sequence learning in healthy volunteers, within a randomised, double-blind, parallel-groups design. Behaviourally, sensitisation was characterised by enhanced subjective responses to amphetamine but did not change performance (i.e. learning rate) during an explicit sequence learning task. In contrast, functional magnetic resonance imaging (fMRI) measurements showed that repeated intermittent amphetamine exposure was associated with increased blood-oxygen-level dependent (BOLD) signal within the medial temporal lobe (MTL) (subiculum/entorhinal cortex) and midbrain, in the vicinity of the substantia nigra/ventral tegmental area (SN/VTA) during sequence encoding. Importantly, MTL hyperactivity correlated with the sensitisation of amphetamine-induced attentiveness. The MTL-midbrain hyperactivity reported here mirrors observations in sensitised rodents and is consistent with contemporary models of schizophrenia and behavioural sensitisation. These findings of meso-hippocampal hyperactivity during AS thus link pathophysiological concepts of dopamine dysregulation to cognitive models of psychosis.